Difference in Severity of Tuberculosis in Children with or without a BCG Scar - Gunadi Santosa; Makmuri Muhammad Syamsuri; I Gusti Gde Djelantik; Elisabeth Projogo; I Gusti Nyoman Gde Ranuh (Paediatrica Indonesiana, 1985)
Tuberculosis can also be found in BCG vaccinated children. An attempt is made to know the difference in severity of tuberculosis in children vaccinated or not vaccinated with BCG.'. Our impression is that tuberculosis occurs less frequent and less severe among BCG vaccinated children compared with unvaccinated children.